Distribution of myrmecochorous species over the landscape and their potential long-distance dispersal by emus and kangaroos - Calvino-Cancela, Maria; He, Tianhua; Lamont, Byron (Blackwell Science, 2008)
Topographical heterogeneity can create a mosaic of substrate types leading to the formation of isolated plant populations. Seed dispersal then becomes crucial for the colonization of such suitable but remote substrate types. We surveyed the distribution of seven elaiosome-bearing species (myrmecochores) over 5 km 2 of natural heathland in southwestern Australia. Ants are the standard means of dispersal of these species, which provide limited dispersal (usually of a few metres). Six species were associated with particular substrate types (dune or swale) and all occurred as discrete populations, on average 270-500 m apart, with closest dune edges 280 m apart. We evaluated the possible roles of emus and kangaroos as alternative agents of long-distance seed dispersal between substrate types. Their droppings contained viable seeds of three of the target species, as well as other myrmecochores, and were evenly distributed over the substrate types. While migration of these plant species between preferred substrate types seems unlikely when considering only their standard dispersal agents (ants), it is highly likely in the presence of emus (in particular) and kangaroos that act as non-standard dispersers. This may have important consequences for plant species conservation by increasing habitat connectivity and favouring regional persistence.